Right ventricular dysfunction assessed by cardiovascular magnetic resonance is associated with poor outcome in patients undergoing transcatheter mitral valve repair. - Maximilian Spieker; Jonathan Marpert; Shazia Afzal; Athanasios Karathanos; Daniel Scheiber; Florian Bönner; Patrick Horn; Malte Kelm; Ralf Westenfeld (PLoS ONE, 2021)
Aims To evaluate whether CMR-derived RV assessment can facilitate risk stratification among patients undergoing transcatheter mitral valve repair (TMVR). Background In patients undergoing TMVR, only limited data exist regarding the role of RV function. Previous studies assessed the impact of pre-procedural RV dysfunction stating that RV failure may be associated with increased cardiovascular mortality after the procedure. Methods Sixty-one patients underwent CMR, echocardiography and right heart catheterization prior TMVR. All-cause mortality and heart failure hospitalizations were assessed during 2-year follow-up. Results According to RV ejection fraction (RVEF) <46%, 23 patients (38%) had pre-existing RV dysfunction. By measures of RV end-diastolic volume index (RVEDVi), 16 patients (26%) revealed RV dilatation. Nine patients (15%) revealed both. RV dysfunction was associated with increased right and left ventricular volumes as well as reduced left ventricular (LV) ejection fraction (all p<0.05). During follow-up, 15 patients (25%) died and additional 14 patients (23%) were admitted to hospital due to heart failure symptoms. RV dysfunction predicted all-cause mortality even after adjustment for LV function. Similarly, RVEDVi was a predictor of all-cause mortality even after adjustment for LVEDVi. Kaplan-Meier survival analysis unraveled that, among patients presenting with CMR indicative of both, RV dysfunction and dilatation, the majority (78%) experienced an adverse event during follow-up (p<0.001). Conclusion In patients undergoing TMVR, pre-existing RV dysfunction and RV dilatation are associated with reduced survival, in progressive additive fashion. The assessment of RV volumes and function by CMR may aid in risk stratification prior TMVR in these high-risk patients.